The Relationship Between the Morphological Characteristics of Aggregates of Selected Phytoplankton Organisms and Their Strength in the Flocculation Process - Kapuścińska, Ewelina; Gryglik, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents the results of research on the strength of "Monoraphidium contortum" and "Microcystis aeruginosa" cell aggregates, with assumption of spherical and fractal structure of the flocs. The method of computer analysis of the microscopic image was used in the research, which made it possible to determine the size and morphological parameters of phytoplankton cell aggregates formed as a result of coagulation with FeCl3. The equivalent diameter and fractal dimension of aggregates allowed us to assess the resistance of the aggregate to shear forces.
Keywords: eutrophic water treatment; coagulation/flocculation; phytoplankton organisms; aggregate strength